Biochar aggravates the negative effect of drought duration on the growth and physiological dynamics of Pinus massoniana - Wang, Xue; Zheng, Wei-Long; Ma, Xiuzhi; Yu, Fei-Hai; Li, Mai-He (Frontiers in Ecology and Evolution, 2023)
Biochar has been considered as a cost-effective amendment to improve the soil water content and thus to mitigate the drought effects on plants. However, less is known about the mitigating effects of biochar application on the negative effect of longer drought duration on trees. We investigated the effects of drought duration in combination with biochar application on the growth, tissue non-structural carbohydrate (NSC) concentrations, needle photosynthesis and δ13C content of one-year-old Pinus massoniana saplings in a greenhouse experiment. We found that the height and total biomass of P. massoniana saplings were significantly decreased with increasing drought duration, which was likely attributed to the suppressed photosynthetic capacity. The longer drought duration (e.g., one month) significantly decreased needle photosynthesis and increased the value of needle δ13C, but did not deplete tissue NSC concentrations in expense of growth, suggesting that plants prioritize carbon storage over growth in response to long duration of drought. Surprisingly, the application of biochar significantly decreased the survival of P. massoniana saplings and aggravated the negative effect of drought duration on the growth of P. massoniana, which, probably, is attributed to the increased soil pH value of >7.5, as P. massoniana is adapted to mildly acid to neutral soils. Our results suggest that the effect of biochar application might be species-specific, and it can aggravate the negative effect of drought duration on plants that are less tolerance to alkaline soils.